A Systematic Review Of Business Ethics And Professional Implementation: A Literacy Study In Digital Marketing - Syakur, Abd.; Safriliana, Retna; Assih, Prihat; Mujairimi, Mujairimi; Bella Ayu, Roro (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The digital era has fundamentally transformed the business landscape, with digital marketing becoming the backbone of many companies' strategies. However, this rapid development has also given rise to significant ethical complexities, demanding deep consideration of business practices and professionalism. This research presents a Systematic Literature Review (SLR) to identify, analyse, and synthesize relevant academic literature on business ethics and professional implementation in the context of digital marketing. A rigorous SLR method is applied, including comprehensive searches in leading scientific databases, screening based on clear inclusion and exclusion criteria, and thematic data extraction and synthesis. The main focus of this review includes crucial issues such as consumer data privacy, transparency in digital advertising, misleading marketing practices, corporate social responsibility (CSR) on digital platforms, and the ethical implications of using artificial intelligence (AI) in marketing. The research findings indicate a gap between technological innovation and an adequate ethical framework, highlighting the urgent need for adaptive regulations, enhanced ethical literacy among practitioners, and the development of a code of ethics specific to the digital realm. The conclusion of this SLR provides critical insights for academics, practitioners, and policymakers to navigate the ethical complexities in the era of digital marketing, promoting more responsible and sustainable practices.